Decision making styles and professionalization of sports: experience of managers of the offices of youth and sports in Yazd province - Nooshin, B.; Nastaran, Y. F.; Saeid, F. M.; Mostafa, E. Z. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
Managers of the Offices of Youth and Sports are part of decision making processes in sports and play a significant role in the development of Professional Sports in the country; as such it seems the analysis of their decision making styles would have a significant importance in the better guidance of the country's sports toward professionalism. The main objective of this research is to study and inspect the decision making styles of the managers of the Offices of Youth and Sports in Yazd Province in relation to the development of Professional Sports in that area. Population and respondents of this research were all the managers and vice managers of the Offices of Youth and Sports in Yazd province the total number of whom was 39. The research method was descriptive and in purpose an applicable one. Instrument for data gathering was the standard survey questionnaire of Scott and Bruce containing 25 questions in order to measure the 5 decision making styles (Rational, Intuitive, Dependent, Spontaneous and Avoidant). The gathered data were analysed using descriptive statistical methods (Mean, Standard Deviation, Charts/Figures) and deductive (non-parametric) methods (Kolmogorov-Smirnov test, Friedman, Spearman and Pearson). The results showed that the Avoidant style of decision making has a greater significance and importance among managers and vice managers of the Offices of Youth and Sports in Yazd province while the Rational style has the least significance among them. It was also found out that there is a significant direct relationship between decision making styles of Rational and Spontaneous; Intuitive and Dependent and the decision making styles of Spontaneous and Avoidant of the managers and vice managers of the Offices of Youth and Sports in Yazd.